2015
DOI: 10.1007/s00792-015-0773-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular peptidases from Deinococcus radiodurans

Abstract: The extremophile Deinococcus radiodurans wild type R1 produces peptidases (metallo- and serine-) in TGY medium and in the media supplemented with human hair (HMY) and chicken feathers (FMY). Enzymatic screening on agar plates revealed peptidase activity. In TGY medium metallopeptidases were detected corresponding to a molecular mass range of 300-85 kDa (gelatinases); 280-130 (caseinases) and a 300 and a 170 kDa (keratinases); and a gelatinolytic serine peptidase (75 kDa). In HMY medium after 144 h, D. radiodur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…However, microbial proteases are among the most important hydrolytic enzymes with great potential for use in various biotechnological processes, as food processing, pharmaceutical products and several other industries (Uddin et al, 2017). Caseinase is used in the food industry as a coagulant in cheese manufacturing and in the reduction of milk allergens, as well as in the energy drinks, dietary foods and health care industry (Dalmaso et al, 2015;Bhaturiwala et al, 2017). Another important protease, gelatinase has played an important role in the food industry, as a meat tenderizer, in the beverage industry, cosmetics and in the development of drugs due to its ability to degrade connective tissue linked to tumor metastasis (Dalmaso et al, 2015;Mohammad et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, microbial proteases are among the most important hydrolytic enzymes with great potential for use in various biotechnological processes, as food processing, pharmaceutical products and several other industries (Uddin et al, 2017). Caseinase is used in the food industry as a coagulant in cheese manufacturing and in the reduction of milk allergens, as well as in the energy drinks, dietary foods and health care industry (Dalmaso et al, 2015;Bhaturiwala et al, 2017). Another important protease, gelatinase has played an important role in the food industry, as a meat tenderizer, in the beverage industry, cosmetics and in the development of drugs due to its ability to degrade connective tissue linked to tumor metastasis (Dalmaso et al, 2015;Mohammad et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Caseinase is used in the food industry as a coagulant in cheese manufacturing and in the reduction of milk allergens, as well as in the energy drinks, dietary foods and health care industry (Dalmaso et al, 2015;Bhaturiwala et al, 2017). Another important protease, gelatinase has played an important role in the food industry, as a meat tenderizer, in the beverage industry, cosmetics and in the development of drugs due to its ability to degrade connective tissue linked to tumor metastasis (Dalmaso et al, 2015;Mohammad et al, 2017). In the diffusion disc antimicrobial susceptibility test, the isolates were sensitive to all antibiotics tested (Table 3), and the results corroborates that microorganisms in natural environments are presumably sensitive to antibiotics (Grenni et al, 2018) and a study performed by Selim et al (2014) in which microorganisms isolated from water and hot spring soils were sensitive to all antibiotics tested.…”
Section: Resultsmentioning
confidence: 99%
“…Extremophiles are considered a valuable source for the production of novel enzymes due to their unique metabolism and ability to withstand extreme environments, such as high temperature, high pressure, high pH and high radiation [13][14][15]. Many studies have been conducted to identify keratinases with excellent properties from extremophiles, such as Nocardiopsis [16], Salicola Marasensis [17] and Meiothermus taiwanensis WR-220 [7].…”
Section: Introductionmentioning
confidence: 99%
“…M. taiwanensis WR-220 was a thermophilic microorganism with a growth temperature of 55-65 • C. The keratinase from this bacterium also exhibited thermal stability, maintaining intact enzymatic activity after 1 h of treatment at 75 • C [7]. It was shown that keratinase genes are present in extreme microorganisms Deinococcus [14], such as D. geothermalis [18] and Deinococcus sp. D7000 [19], and that the feather-degrading bacteria D. ficus [20] and D. radiodurans R1 [14] are able at 30 • C to degrade intact feathers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation